2022
DOI: 10.1080/21655979.2022.2074106
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0008068 facilitates the oral squamous cell carcinoma development by microRNA-153-3p/acylgycerol kinase (AGK) axis

Abstract: Oral squamous cell carcinoma (OSCC) is a common cancer with high recurrence, metastasis rates and poor prognosis. Circular RNAs (circRNAs) take part in regulating OSCC. Herein, we examined the role of circ_0008068 in OSCC. The circ_0008068, Katanin p60 ATPase-containing subunit A-like 1 (KATNAL1) mRNA, microRNA-153-3p (miR-153-3p) and acylgycerol kinase (AGK) contents were indicated by quantitative real-time polymerase chain reaction (qRT-PCR) and western blot. Moreover, in vitro and in vivo assays were conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Recent studies have also shown that circRNAs can regulate immune metabolism of HNSCC, and circ_0008068 may affect glycolysis by targeting mir-153-3p/acylglycerol kinase (AGK) axis and facilitate the CD8 + T cell response ( 159 ). It provides a better understanding of the interaction between HNSCC cellular immunity and metabolic rate, and we look forward to opening up new immune-related therapies for HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown that circRNAs can regulate immune metabolism of HNSCC, and circ_0008068 may affect glycolysis by targeting mir-153-3p/acylglycerol kinase (AGK) axis and facilitate the CD8 + T cell response ( 159 ). It provides a better understanding of the interaction between HNSCC cellular immunity and metabolic rate, and we look forward to opening up new immune-related therapies for HNSCC.…”
Section: Discussionmentioning
confidence: 99%